Perlindungan Hukum Terhadap Masyarakat dari Konsumsi Obat Mengandung NDMA di Kota Semarang - Rakasyiwa Rewangga Sukma; Adi Suliantoro (Fakultas Hukum Universitas Stikubank, 2021)
September 13, 2019, the US Food and Drug Administration (FDA) and the European Medicine Agency (EMA) issued a warning through the official FDA website, that contaminants were found that were thought to trigger cancer. It is known that the contamination is an impurity or nitrosamine compound or commonly called N-Nitrosodimethylamine (NDMA) which is included in chemical contamination originating from chemical elements or compounds that can endanger human health. Symptoms that appear are the skin and the whites of the eyes turning yellow, fatigue, darker urine, and abdominal pain. Based on this, there is a problem that needs to be analyzed, namely how the law protects consumers from consuming these materials, especially in the city of Semarang, are there any obstacles in the effort to protect consumers from consuming drugs containing NDMA. The methodology used in this research is juridical normative with secondary data, which is analyzed by analytical descriptive. The results of the analysis, it is known that the state through various provisions has protected consumers from consuming hazardous materials, including those in Article 8